2020
DOI: 10.35313/ijabr.v2i01.80
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the International and Domestic Tourists Behavior in Australia

Abstract: Tourism contributes to regional development and generates income for destinations. However, in many cases, the growth of tourist numbers does not necessarily result in an equivalent rise in economic contribution. The search for quality tourists over the quantity of tourists is certainly an important goal of regional development managers, but the efforts required to implement such an approach, especially the detailed documentation of tourist behavior while visiting the region, pose a challenge for most. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
1
Order By: Relevance
“…The Great Ocean Road is a scenic coastal drive that contributes up to 6.1% of revenue to the regional economy 51 . It attracts more than 5,000,000 visitors annually, and Apollo Bay is the second most popular visitor destination 51 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Great Ocean Road is a scenic coastal drive that contributes up to 6.1% of revenue to the regional economy 51 . It attracts more than 5,000,000 visitors annually, and Apollo Bay is the second most popular visitor destination 51 .…”
Section: Resultsmentioning
confidence: 99%
“…The Great Ocean Road is a scenic coastal drive that contributes up to 6.1% of revenue to the regional economy 51 . It attracts more than 5,000,000 visitors annually, and Apollo Bay is the second most popular visitor destination 51 . The spatial distribution of transect-specific r-BCDs indicates three distinctive zones where behavioural regimes are mostly mixed (M), erosional (E) or depositional (D) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous studies have suggested that temporary exhibitions of modern art have a positive impact on tourism [8]. Therefore, if we want to quantitatively analyze the impact of exhibitions on sustainable tourism (i.e., exhibition-driven tourism), then the number of tourists is a clear and direct indicator [9][10][11]. Second, the tourism industry has emerged as a key force for sustainable (socioeconomic) development globally [12].…”
Section: The Logical Model and Purposementioning
confidence: 99%
“…While common ground remains existential, multiple studies have suggested a difference between domestic and international tourists in evaluating their destination preference. The phenomena is further extended towards the visitors' behavioural inclination upon their visitation, in terms of monetary spending, lodging duration and geographical excursion (Dean, Novianti, & Noor, 2020). Cultural predisposition is inevitably highlighted where lower rating among international tourists towards a travelling experience as compared to their domestic counterpart has been the result of diminished cultural congruency and local interactivity.…”
Section: The Moderating Effect Of Nationalitymentioning
confidence: 99%